ESG PERFORMANCE AND CARBON DISCLOSURE EFFECTIVENESS: INSIGHTS FROM A SYSTEMATIC REVIEW OF CARBON EMISSION INTENSITY STUDIES - Chasbiandani, Tryas; Yusuf, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
Abstract: This study aims to systematically review empirical evidence on the influence of Environmental, Social, and Governance (ESG) practices and carbon disclosure on carbon emission intensity (CEI). The research problem arises from inconsistent findings across previous studies regarding whether ESG and disclosure effectively reduce emission intensity. Using a systematic literature review (SLR) approach, sixty empirical studies published between 2017 and 2025 were analyzed based on their research design, context, analytical method, and the direction of ESG–CEI relationships. The analysis reveals heterogeneous results: 27% of studies found a negative relationship, 22% a positive relationship, and the rest mixed or insignificant effects. Regression-based methods dominate the empirical approaches, particularly multiple linear regression and panel data analysis. These findings suggest that the impact of ESG and disclosure on CEI varies depending on contextual factors such as regulatory environment, industry characteristics, and disclosure quality. The study concludes that while ESG performance tends to contribute to emission reduction, its effectiveness remains conditional and context-dependent. Future research should focus on causal identification, longitudinal design, and emerging markets to better clarify the decarbonization potential of ESG practices.